Informetrics : theory, methods and applications - Qiu, Junping; Zhao, Rongying; Yang, Siluo; Dong, Ke (Springer, 2017)
This book provides an accessible introduction to the history, theory and techniques of informetrics. Divided into 14 chapters, it develops the content system of informetrics from the theory, methods and applications; systematically analyzes the six basic laws and the theory basis of informetrics and presents quantitative analysis methods such as citation analysis and computer-aided analysis. It also discusses applications in information resource management, information and library science, science of science, scientific evaluation and the forecast field. Lastly, it describes a new development in informetrics- webometrics. Providing a comprehensive overview of the complex issues in today's environment, this book is a valuable resource for all researchers, students and practitioners in library and information science.